Análise sistêmica das relações de poder em grupos de liderança oficial de Igrejas de governo congrecional:estudos de caso em Igrejas Memonitas de Curitiba - Friesen, Albert (2009)
The following research has "power" as its object of study, specifically in the form of "power relations" in the governing councils (pastoral and administrative) of Mennonite churches in Curitiba. The presumed form of government of these churches is historically congregational, that is, the assemblies of the respective churches are supreme and ultimate in deliberation. The research methodology is sociological, inductive, functionalist, with phenomenological tendencies, having as main perspective the systemic theory and its research resources. General systems theory guides the foundations of research, social systems theory is the framework for research. The research method is participant observation with video and audio recordings, transcription, analysis and conclusion drawing. The research technique cited proved to be effective and useful for data collection in field research dealing with groups and their different functions in ecclesiastical groups. The objectives seek to identify the systemic dynamics in the meetings of the observed councils, as well as to identify the process of power relations in the same councils.The assumptions made as a starting point state that systemic theory in any perspective is observable, and the elements (advisers) of power relations are unaware of their acts of power. The main and secondary hypotheses were confirmed by participant observation, namely: the research verifies the general hypothesis that even churches and their social systems evidence systemic principles according to Niklas Luhmann's general theory of systems and social systems theory. The specific hypotheses verify whether the advisers of the leadership groups show awareness of the power exercised and the power implicit in their roles and roles; whether formal groups elected by the assembly exercise de facto power or whether there is influence from informal power; whether there is a correlation between formal power and "rigid boundaries", informal power and "diffuse boundary"; if it is possible to work preventively and interventionally through the concept of power relations and systemic social principles. Curitiba's Mennonite churches generally preserve traces of congregational government, but the transition to pastoral and autocratic styles of government from the observed councils is a fact and seems irreversible. Apparently the causality of this movement arises in the metropolitan social context and its implications, rather than in a change strategically planned by the leaders. Therefore, the transition seems to be cultural. In fact, the social transformations of the Mennonite traditions are directly proportional to their inclusion and inculturation in the social context in which they are situated, thus confirming the systemic principles of society in general. (AU)